A national outbreak of Serratia marcescens complex: investigation reveals genomic population structure but no source, Norway, June 2021 to February 2023 - The Norwegian Serratia study group (Eurosurveillance)
We report a national outbreak of Serratia marcescens complex type 755 (ct755) in Norway, with 74 cases identified between June 2021 and February 2023. Careful reviews of patient journals and interviews were performed, involving 33 hospitals throughout Norway. All available clinical isolates of S. marcescens collected between January 2021 and February 2023 (n = 455, including cases) from all involved hospitals were whole genome sequenced. Cases displayed a pattern of opportunistic infections, as usually observed with S. marcescens. No epidemiological links, common exposures or common risk factors were identified. The investigation pointed to an outbreak source present in the community. We suspect a nationally distributed product, possibly a food product, as the source. Phylogenetic analysis revealed a highly diverse bacterial population containing multiple distinct clusters. The outbreak cluster ct755 stands out as the largest and least diverse clone of a continuum, however a second cluster (ct281) also triggered a separate outbreak investigation. This report highlights challenges in the investigation of outbreaks caused by opportunistic pathogens and suggests that the presence of identical strains of S. marcescens in clinical samples is more common than previously recognised.